Consumers' pro-environmental behaviour impacts on the choice and WTP for innovative sustainable food packaging. - Nur Hafizah Muhammad (2019)
The growing awareness of the environmental damage associated with food product packaging waste has led the public to a keen interest in the development of sustainable packaging. The development of sustainable packaging capable of reducing packaging waste may contribute to slowing down environmental damage caused by current unstainable packaging material. However, previous research in consumer behaviour shows that not all sustainable attributes of food packaging would encourage consumers’ decision-making towards more sustainable choices. This pattern might be explained by the lack of understanding on behalf of the food industry and policymakers of what sustainable packaging attributes consumers prefer and of what motivations can influence consumers’ preferences and willingness to pay (WTP) towards innovative sustainable packaging. To fill such a gap, this study aims to explore how consumers’ pro-environmental behaviour affect their purchasing decisions in the context of innovative sustainable food packaging in the UK. A psychology environmental theory (value-belief-norm) was combined with stated choice methods to assess how consumers’ values and beliefs of environmental concern and personal norms influence WTP for new bioplastic food packaging obtained from agricultural waste and tree cellulose. To assess consumer preferences and WTP for this innovative eco-friendly packaging material stated choice experiment on innovative milk packaging and contingent valuation on innovative bioplastic material packaging were applied to their basket of food products. Data were collected online and was administered to a sample of 600 UK respondents. Structural equation modelling was performed to confirm the goodness of fit of the proposed conceptual framework, while mixed logit model and Tobit model were used to estimate WTP for eco-friendly packaging. Results indicate that environmental values and beliefs together with socio-demographic characteristics of respondents influenced consumers’ pro-environmental purchasing behaviour subjectively. Purchasing decisions were influenced positively by female, young and married respondents with knowledge of bioplastic packaging material. On the average participants were WTP £2.72 extra for bioplastic packaging in food products. Respondents also showed to prefer sustainable packaging made from certified agricultural waste because of its recyclable and biodegradable characteristics. The study also found empirical evidence that some consumers tend to use attribute cut-offs in decision-making and thus to support the hypothesis that ignoring cut-off attributes in the estimation model may generate biased estimates.